2012
DOI: 10.1111/j.1538-7836.2012.04767.x
|View full text |Cite
|
Sign up to set email alerts
|

Platelet factor 4 platelet levels are inversely correlated with steady‐state platelet counts and with platelet transfusion needs in pediatric leukemia patients

Abstract: To cite this article: Lambert MP, Reznikov A, Grubbs A, Nguyen Y, Xiao L, Aplenc R, Rauova L, Poncz M. Platelet factor 4 platelet levels are inversely correlated with steady‐state platelet counts and with platelet transfusion needs in pediatric leukemia patients. J Thromb Haemost 2012; 10: 1442–6.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
5
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 12 publications
(35 reference statements)
1
5
0
Order By: Relevance
“…PF4 content influences megakaryopoiesis in mice and patients and HSC replication . These findings imply that there is steady‐state free PF4 within the BM intramedullary space, and the level of free PF4 increases under stress.…”
Section: Resultssupporting
confidence: 91%
See 1 more Smart Citation
“…PF4 content influences megakaryopoiesis in mice and patients and HSC replication . These findings imply that there is steady‐state free PF4 within the BM intramedullary space, and the level of free PF4 increases under stress.…”
Section: Resultssupporting
confidence: 91%
“…PF4 expression has been noted in other hematopoietic lines , but the RNA levels show ≥2 orders of magnitude less abundant expression than in megakaryocytes , where PF4 is the third most abundant mRNA and the protein makes up 3% of granular content . We and others have shown that PF4 has an important intramedullary function in regulating the number of megakaryocytes: platelet PF4 levels are inversely related to steady‐state platelet counts ; the degree of both chemotherapy and radiation‐induced thrombocytopenia in murine models is inversely related to PF4; and the level of PF4 expression in platelets inversely correlates with the need for transfusion after chemotherapy in patients . This negative paracrine effect of PF4 on megakaryocytes is mediated by low‐density lipoprotein receptor–related protein 1 (LRP1, CD91) .…”
Section: Introductionmentioning
confidence: 99%
“…Use of eltrombopag in severe aplastic anemia has demonstrated interesting effects on both platelet and stem cell populations and further studies are ongoing to better understand these findings and to define patient populations. We have previously shown that PF4 levels inversely correlate with platelet transfusion need and platelet count nadir in pediatric patients with leukemia (whereas TPO levels did not correlate), 11 and baseline TPO levels in our various murine models with different PF4 expression levels also do not correlate with platelet counts or platelet count recovery. Current studies are under way to determine whether TPO stimulation would complement blocking PF4 or whether stimulating megakaryopoiesis by TPO administration might have a deleterious effect on count recovery by enhancing marrow-PF4 release.…”
mentioning
confidence: 84%
“…2,[6][7][8] Our previous studies have shown that endogenous levels of a platelet-specific chemokine, platelet factor 4 (PF4; CXCL4) are inversely correlated with bone marrow recovery after radiation injury. 9 PF4 is a known mediator of megakaryopoiesis, plays an important role in the negative regulation of megakaryopoiesis, [10][11][12] and is found at high concentrations intramedullary, allowing it to act locally within the bone marrow niche in a negative paracrine fashion to regulate local megakaryocytes 13 and stem cells. 14 We have also previously shown that this effect on megakaryopoiesis by PF4 can be blocked by preventing PF4 binding to cell surfaces using anti-PF4 antibodies or unfractionated heparin (UFH) in vitro 10,12 and F(ab9) 2 fragments of these antibodies in vivo, likely due to their ability to penetrate into the marrow.…”
Section: Introductionmentioning
confidence: 99%
“…Prognosis CXCL4 may be a useful biomarker predicting the risk of thrombocytopenia developing with chemotherapy (CIT) (Lambert et al, 2012). Patients with low steady-state platelet CXCL4 levels would better tolerate chemotherapy, whereas high concentrations may be an indication for CIT and predict the need for a platelet transfusion.…”
Section: Chemotherapy-induced Thrombocytopenia (Cit)mentioning
confidence: 99%